El binomio degeneración-regeneración en las élites intelectuales espiritualistas de principios del siglo XX en Centroamérica - Casaús Arzú, Marta (Revista Complutense de Historia de América, 2010)
The article analyzes the impact of the degenerationist and regenerationist theories in Latin America, with a special emphasis on Guatemala, focusing on the conceptual shift, among the intellectual elites, with regard to their concept of race, culture, ethnicity and regeneration. It also analyzes other conceptions derived from this binomer, such as new man, Latin and Anglosaxon race and the conception assumed by the indigenous elites regarding the regeneration of their race.
Keywords: Degeneration; Regeneration; Race; Nation; Intellectual Elites; Spiritualism; Theosophy; Regenerationism; Indigenous Elites; Guatemala; 20th Century